A disturbing trend: An analysis of the decline in surgical critical care fellowship training of Black and Hispanic surgeons. Issue 1 (28th July 2022) - Hambrecht, Amanda; Berry, Cherisse; DiMaggio, Charles; Chiu, William; Inaba, Kenji; Frangos, Spiros; Krowsoski, Leandra; Ricketts Greene, Wendy; Issa, Nabil; Pugh, Carla; Bukur, Marko
Abstract : Underrepresented minorities in medicine are disproportionally present in Surgical CC training. From 2005-2020, Black + Hispanic men/women had significantly lower graduation rates and annual decline in graduation compared to Whites. #DiversityInSurgery#ILookLikeASurgeon#SeeItBeIt Abstract : BACKGROUND: Underrepresented minorities in medicine (URiMs) are disproportionally represented in surgery training programs. Rates of URiMs applying to and completing General Surgery residency remain low. We hypothesized that the patterns of URiMs disparities would persist into surgical critical care (SCC) fellowship applicants, matriculants, and graduates. METHODS: We performed a retrospective analysis of SCC applicants, matriculants, and graduates from 2005 to 2020 using the graduate medical education resident survey and analyzed applicant characteristics using the Surgical Critical Care and Acute Care Surgery Fellowship Application Service from 2018 to 2020. The data were stratified by race/ethnicity and sex. Indicator variables were created for Asian, Hispanic, White, and Black trainees. Yearly proportions for each race/ethnicity and sex categories completing or enrolling in a program were calculated and plotted over time with Loess smoothing lines and overlying 95% confidence bands. The yearly rate and statistical significance of change over time were tested with linear regression models with race/ethnicity and sex proportion as the dependent variables and year as the explanatory variable. RESULTS: From 2005 to 2020, there were a total of 2, 481 graduates. Black men accounted for 4.7% of male graduates with a significant decline of 0.3% per year for the study period of those completing the fellowship ( p = 0.02). Black women comprised 6.4% of female graduates and had a 0.6% decline each year ( p < 0.01). A similar trend was seen with Hispanic men, who comprised 3.2% of male graduates and had a 0.3% annual decline ( p = 0.02). White men had a significant increase in both matriculation to and graduation from SCC fellowships during the same interval. Similarly, Black and Hispanic applicants declined from 2019 to 2020, while the percentage of White applicants increased. CONCLUSION: Disparities in URiMs representation remain omnipresent in surgery and extend from residency training to SCC fellowship. Efforts to enhance the recruitment and retention of URiMs in SCC training are warranted. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; level IV. Abstract :